Economic model building - Neal, Frank; Shone, Robert Minshull, Sir (London : Macmillan Press, 1976)
This book is about the process of building positive economics models. It is addressed primarily to economists and would-be economists. It bases itself firmly on scientific method and considers components of models, static and dynamic and policy models and the associated problems of statistical estimation from non-experimental data. For its intended main audience it is an excellent book, suitable for anyone who has mastered an introductory, model-based course in Economics.
Includes index.
Includes bibliographical references: p. [168]
rpm 12/04/2018
Loans
Keywords: Economics